Rapid screening of Alternaria mycotoxins using MALDI‐TOF mass spectrometry. (26th April 2016) - Sivagnanam, Kumaran; Komatsu, Emy; Rampitsch, Christoph; Perreault, Hélène; Gräfenhan, Tom
Abstract: BACKGROUND: Members of the Alternaria genus produce various toxins whose occurrence in agricultural commodities is a major concern for humans and the environment. The present study developed a simple and efficient matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) method for the rapid detection of Alternaria toxins. RESULTS: A new method for the detection of alternariol (AOH), alternariol monomethyl ether (AME) and tentoxin (TEN) by MALDI‐TOF MS was developed. Different solid phase extraction (SPE) clean‐up methods were tried to optimize the purification of wheat matrix, and an optimal extraction method was designed to recover the three Alternaria toxins. In addition, various MALDI matrices were examined and α ‐cyano‐4‐hydroxycinnamic acid (CHCA) matrix gave good repeatability for all three Alternaria toxins. CONCLUSION: This is the first study to report the detection of three important Alternaria toxins concurrently using MALDI‐TOF MS and opens up the possibility of rapid screening of Alternaria toxins in several other cereals and food products. © 2016 Her Majesty the Queen in Right of Canada Journal of the Science of Food and Agriculture © 2016 Society of Chemical Industry